Pemberdayaan Masyarakat Desa Ternadi Melalui Optimalisasi Pemanfaatan Pekarangan Tanaman Hortikultura dengan Memanfaatkan Pupuk Organik : Indonesia - Widyastuti, Winda; Ariyanto, Shodiq Eko; Prakoso, Tangguh; Murrinie, Endang Dewi (UII, 2025)
Utilizing yard land is one approach to achieving food security. Well-maintained yards can become comfortable, aesthetic, and healthy environments, one of which is by using them to grow horticultural plants, especially those that can be consumed daily. This community service activity, aimed at empowering the foster village, seeks to enhance the knowledge of the PKK women in Ternadi Village about the utilization of yards with horticultural plants and to provide knowledge and skills on how to make organic fertilizer. The methods used in this community service activity include surveys, counseling, discussions, practice, and evaluation. In general, the activities conducted have successfully increased the partner group's knowledge about yard utilization with horticultural plants and enhanced their understanding of the potential use of organic waste as a planting medium and fertilizer in the form of compost and liquid organic fertilizer.